Incidence and impact of community respiratory viral infections in post‐transplant cyclophosphamide‐based graft‐versus‐host disease prophylaxis and haploidentical stem cell transplantation. (14th June 2021) - Mulroney, Carolyn M.; Abid, Muhammad Bilal; Bashey, Asad; Chemaly, Roy F.; Ciurea, Stefan O.; Chen, Min; Dandoy, Christopher E.; Diaz Perez, Miguel A.; Friend, Brian D.; Fuchs, Ephraim; Ganguly, Siddhartha; Goldsmith, Scott R.; et al.
Summary: Community respiratory viral infections (CRVIs) are associated with pulmonary function impairment, alloimmune lung syndromes and inferior survival in human leucocyte antigen (HLA)‐matched allogeneic haematopoietic stem cell transplant (HCT) recipients. Although the incidence of viral infections in HLA‐haploidentical HCT recipients who receive post‐transplant cyclophosphamide (PTCy)‐based graft‐ versus ‐host disease (GVHD) prophylaxis is reportedly increased, there are insufficient data describing the incidence of CRVIs and the impact of donor source and PTCy on transplant outcomes. Analysing patients receiving their first HCT between 2012 and 2017 for acute myeloid leukaemia, acute lymphoblastic leukaemia and myelodysplastic syndromes, we describe comparative outcomes between matched sibling transplants receiving either calcineurin‐based GVHD prophylaxis (SibCNI, N = 1605) or PTCy (SibCy, N = 403), and related haploidentical transplants receiving PTCy (HaploCy, N = 757). The incidence of CRVIs was higher for patients receiving PTCy, regardless of donor type. Patients in the HaploCy cohort who developed a CRVI by day +180 had both a higher risk of treatment‐related mortality [hazard ratio (HR) 2⋅14, 99% confidence interval (CI) 1⋅13–4⋅07; P = 0⋅002] and inferior 2‐year overall survival (HR 1⋅65, 99% CI 1⋅11–2⋅43; P = 0⋅001) compared to SibCNI with no CRVI. This finding justifies further research into long‐term antiviral immune recovery, as well as development of preventive and treatment strategies to improve long‐term outcomes in such patients.